2017
DOI: 10.1093/neuonc/nox197
|View full text |Cite
|
Sign up to set email alerts
|

Exercise ameliorates neurocognitive impairments in a translational model of pediatric radiotherapy

Abstract: Our data strongly suggest that exercise may be useful in combination with interventions aimed at improving cognitive outcome following pediatric CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
5
35
0
Order By: Relevance
“…We did not observe any significant changes in FA or RD in the different brain regions following CRT or interactive effects between CRT and sex between the animals. These findings are similar to our results in rats when we did not find significant changes in FA but detected connectome differences due to CRT and exercise ( Sahnoune et al, 2018 ). Similarly, others have also reported difficulty in measuring differences in FA in animal models of CRT ( Wang et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We did not observe any significant changes in FA or RD in the different brain regions following CRT or interactive effects between CRT and sex between the animals. These findings are similar to our results in rats when we did not find significant changes in FA but detected connectome differences due to CRT and exercise ( Sahnoune et al, 2018 ). Similarly, others have also reported difficulty in measuring differences in FA in animal models of CRT ( Wang et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Prior to examining long-term damage to the brain, we observed radiation-induced decreases in body lengths at 3 months post-CRT and weights over time. Our group has previously observed this in rats irradiated as juveniles ( Rodgers et al, 2016 ; Sahnoune et al, 2018 ), with a similar consistent lower body weight in irradiated animals in comparison to shams. Further, the present study demonstrated sex differences in body weight with no interaction with CRT: adult male mice consistently weighed more than females.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Brain-derived neurotropic factor plays a key role in supporting neuronal development and function, so this phenomenon may be clinically relevant. A recent report showed preliminary evidence that reduction in neuroinflammation might be one of the effects of voluntary exercise that works toward ameliorating the radiation-induced cognitive decline observed in a rodent model of cranial irradiation [51]. This persistent neuroinflammation may also be in part responsible for shunting remaining viable neuronal precursor cells toward a glial fate [52,53].…”
Section: Particle Therapy Induced Neuroinflammation and Effects On Glmentioning
confidence: 99%